Inside Cover, Volume 115, Issue 5. Issue 5 (5th February 2015) - Nakai, Hiromi; Tsuneda, Takao
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> REIN (Replica‐exchange interface) is interface software for Replica‐exchange molecular dynamics (REMD) simulations, utilizing existing MD software without any modification. It handles the exchange of replicas in REMD, Replica‐exchange umbrella sampling (REUS, ) and multidimensional REMD (MREMD) simulations. Naoyuki Miyashita, Suyong Re, and Yuji Sugita (DOI: 10.1002/qua.24785) use an alanine‐pentapeptide in water to demonstrate the performance of REIN. The efficiency is compared to various REMD techniques for computing free‐energy landscapes of this peptide using REIN. In the upper figures, the alaninepentapeptide system and the reaction coordinate in REUS and MREMD simulations are shown. An image of replica‐exchanges in MREMD simulations is shown in the lower figure.